Thermal Analysis in Gas Insulated Transmission Lines Using an Improved Finite-Element Model - Xiaowen WU; Naiqiu SHU; Hongtao LI; Ling LI (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In this paper, an improved finite element (FE) model is proposed to investigate the temperature distribution in gas insulated transmission lines (GILs). The solution of joule losses in eddy current field analysis is indirectly coupled into fluid and thermal fields. As is different from the traditional methods, the surrounding air of the GIL is involved in the model to avoid constant convective heat transfer coefficient, thus multiple species transport technique is employed to deal with the problem of two fluid types in a single model. In addition, the temperature dependent electrical and thermal properties of the materials are considered. The steady-state and transient thermal analysis of the GIL are performed separately with the improved model. The corresponding temperature distributions are compared with experimental results reported in the literature. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1247